2022
DOI: 10.3934/allergy.2022016
|View full text |Cite
|
Sign up to set email alerts
|

Contrast allergies for neurological imaging: When to proceed

Abstract: <abstract> <p>Contrast-enhanced neuroimaging is often necessary for the diagnosis and care of patients with diseases of the central nervous system. Although contrast is generally well tolerated and allergy to contrast is rare, allergic reactions can be severe and life threatening. Therefore, physicians should take care to prevent severe contrast allergy. In this review, we will discuss contrast allergy as well as potential strategies to reduce the risk of severe reactions in patients who require ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…The simultaneous detection of high concentrations of iodinated contrast medium in CSF and serum supports contrast medium extravasation rather than hemorrhage. In addition, the exclusion of contrast allergy or allergic-like reactions is also essential for the diagnosis of CIE. A recent study showed that allergic-like or allergic reactions caused by contrast media are rare, which can be severe or even life-threatening ( Fusco et al, 2022 ). It is important to obtain a history of immediate or delayed reactions to a specific contrast medium, which may contribute to predicting the risk for future reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous detection of high concentrations of iodinated contrast medium in CSF and serum supports contrast medium extravasation rather than hemorrhage. In addition, the exclusion of contrast allergy or allergic-like reactions is also essential for the diagnosis of CIE. A recent study showed that allergic-like or allergic reactions caused by contrast media are rare, which can be severe or even life-threatening ( Fusco et al, 2022 ). It is important to obtain a history of immediate or delayed reactions to a specific contrast medium, which may contribute to predicting the risk for future reactions.…”
Section: Discussionmentioning
confidence: 99%